Evaluation of a new diagnostic immunohistochemistry approach for ROS1 rearrangement in non-small cell lung cancer. (August 2020) - Wang, Wenxian; Cheng, Guoping; Zhang, Gu; Song, Zhengbo
Highlights: IHC assay is an effective and convenient tool for detecting ROS1 gene expression. A new IHC (1A1) assay is more reliable than IHC D4D6 for detecting ROS1 expression. The sensitivity and specificity of IHC 1A1 were 100 % and 99.5 % for RT-PCR assay. Abstract: Background: ROS1 rearrangement is an oncogenic driver of non-small cell lung cancer (NSCLC). Accurate detection of ROS1 rearrangements in clinical tumor samples is vital. In this study, a new immunohistochemistry (IHC) monoclonal antibody (mAb) 1A1 assay was evaluated in patients with NSCLC. Methods: A cohort (cohort A) of 22 positive ROS1 reverse transcription-polymerase chain reaction (RT-PCR) samples were studied to evaluate the IHC-1A1 assay by comparing IHC-D4D6 mAb and another cohort (cohort B) of 178 consecutive cases to verify the assay by comparison using the RT-PCR method. IHC results with 2+ (H-score > 100) or 3+ staining was considered ROS1-positive. Results: In cohort A, ROS1 protein expression was evaluated in 22 samples by IHC-D4D6 and IHC-1A1 assays. For IHC-1A1, one patient was 1+ and 11 patients were 1+ for IHC-D4D6. ROS1 2–3+ was found in 36.4 % (8/22) of samples with IHC-D4D6 and 90.9 % (20/22) with IHC-1A1.The mean H-score of the 1A1 ROS1 2-3+ cases was 203.5. With the D4D6 clone, the mean H-score of the D4D6 ROS1 2∼3+ cases was 182.5. In the 178 NSCLC patients in cohort B, ROS1 rearrangement was detected with IHC and RT-PCR assays. Two patients had tumors with ROS1 IHC-1A1 3+ and one patient was IHC-1A1 2+. Among the three patients, two were confirmed to have ROS1 rearrangement by RT-PCR. None of the 175 ROS1 IHC-1A1 0–1+ samples were ROS1-positive by RT-PCR. Conclusions: The results showed that the new IHC-1A1 ROS1 clone is a sensitive preliminary method and may be another excellent screening method in addition to the original IHC detection method to detect ROS1 gene rearrangements.